Pengaruh Manajemen Sumber Daya Manusia (SDM) Terhadap Peningkatan Kinerja Guru Di MTs. Al-Fath Gebang - Dwi Mahriza, Rani Febriyanni, Indra Syahputra (Pusdikra Publishing, 2023)
An educational institution in realizing its existence in order to achieve a goal requires effective human resource management (HR). The correlation of HR management with teacher performance is two things that are very related and cannot be separated. This means that the ability to empower human resources in an educational institution will lead to improvements in teacher performance at the school, one of which is the development of human resource management programmed for teacher performance by the head of Madrasah Tsanawiyah Al-Fath Gebang. Based on the research problems that have been formulated and the results of the research that the researchers have done, the Level of Human Resource Management on teacher performance in MTs. Al-Fath Gebang Islamic Boarding School can be said to be very good. This can be seen from the acquisition of table percentages from the frequency distribution which all place teacher performance a) Intellectual quality including knowledge and skills), b) Education, c) Understanding of the field, d) Ability. In high level . This means that teacher competence is needed, especially in the learning process, not only one competency that must be mastered but strived to have all four of these competencies. There is an overall positive and significant influence of human resource management on teacher performance in MTs. Al-Fath Gebang Islamic Boarding School. This shows that human resource management is very much needed in the process of improving teacher performance.